FEAR AND FEELING OF INSECURITY IN HOTELS AND HOST COMMUNITIES, IBADAN, NIGERIA - Gbenga John OLADEHINDE; Adeola Francisca OLADELE; Lateef Adeleke ADENIYI; Olubunmi Lukman LAWAL (Analele Universităţii din Oradea: Seria Geografie)
The study examines fear and feeling of insecurity in Ibadan, Nigeria. Residents and staff of hotels were selected through multistage and purposive sampling respectively. The study discovered that the mean relative frequency worry index (RFWI) among the hotel staff was 2.54, while it was 2.44 among the residents of the host communities. The result showed that theft, fraud, robbery sexual abuse, and burglary were the most frequently worried crime in the hotel industry while robbery, theft, fraud, burglary, and sexual abuse were highly worried among the residents of host communities. Using factor analysis, 82.28% of the total variance which comprises mechanical/personal (42.7%), human (19.5%), economic (11.53%), and environmental factors (8.49%) were the factors influencing fear and feeling of insecurity among hotel staff while human/personal (49.30%), economic (11.26%), mechanical (7.49%), and environmental factor (6.52%), representing 74.5% of the whole variance were the factors among the residents of the host communities. The study concluded that fear and feeling of insecurity is associated with different factors.